Development of a Digital-Based Assessment of Key Competencies for Transformation toward Sustainability: Multi-Assessment Evidence - Chaiwichit Chianchana; Sageemas Na Wichian (Emerging Science Journal)
The objectives of this research were to develop a digital-based assessment system for evaluating key competencies for transformation toward sustainability, review the assessment system, examine the dimensions by analyzing multidimensionality, and make predictions using logistic regression analysis. The sample consisted of 449 students for the needs study, 10 experts for system development and assessment, 38 students for system assessment, and 674 students to examine the key competencies. The instruments used were a questionnaire, a focus group discussion record form, an assessment form for students and experts, and an assessment in the digital-based system. Data were analyzed using content analysis, mean, standard deviation, multidimensional analysis, and logistic regression analysis. The results of the research showed the following: 1) Students and experts must develop a digital assessment system. 2) A digital-based assessment system should be developed. This involved personalized assessment through the website. The assessment results were obtained in real-time, and development suggestions regarding each competency were incorporated. The use of the digital-based assessment system demonstrated that the screen, terminology, system information, and system capabilities were at a good level. The experts’ assessment showed that the heuristic was at a good level, whereas the utility, interpretation, and accuracy of the system were deemed to be very good. 3) The evidence of the key competencies was multidimensional. In addition, the predictive model regarding academic achievement was consistent with the empirical data, in that seven competencies could be predicted, but two competencies could not. The model predicts academic success 68.50% of the time.